2020
DOI: 10.1080/13683500.2020.1846504
|View full text |Cite
|
Sign up to set email alerts
|

On the choice of accommodation type at the time of Covid-19. Some evidence from the Italian tourism sector

Abstract: This note focuses on the impact of coronavirus on Italian tourism. Using a sample of 1056 travellers, we find a positive relationship between the security of destination and the probability to accommodate in hotels and B&B. Furthermore, regional contagion is negatively associated to the willingness to pay for accommodation services. The policy implications are twofold. Firstly, hotels/B&B claim for financial support to ensure social distancing and, thus, security that will attract tourists. Secondly, public fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 8 publications
4
25
0
3
Order By: Relevance
“…In the Spanish hospitality industry, economic and tourism activities are generating an economic crisis [72]. In Italy, hotels and bed and breakfasts require financial support [73]. In India, the discussion database papers analyzed the hospitality industry during the pandemic; the first three themes were the recovery of the hospitality industry, market demand and the loss of revenue [74].…”
Section: The Hospitality Industry and The Covid-19 Pandemicmentioning
confidence: 99%
“…In the Spanish hospitality industry, economic and tourism activities are generating an economic crisis [72]. In Italy, hotels and bed and breakfasts require financial support [73]. In India, the discussion database papers analyzed the hospitality industry during the pandemic; the first three themes were the recovery of the hospitality industry, market demand and the loss of revenue [74].…”
Section: The Hospitality Industry and The Covid-19 Pandemicmentioning
confidence: 99%
“…In this regard, it should be noted that the data also shows that some of the people within this cluster tended to travel to less crowded destinations in which they might have practiced outdoor activities; hence, their complete avoidance might be related to the type of travel these people are used to experiencing. In other words, they might have reported no changes to their holiday habits due to the fact that travelling to less crowded places was already one of their travel habits, even before the pandemic, hence their perception of risks due to travelling was low and they believed themselves to be less vulnerable compared to tourists travelling to more crowded destinations (Aiello et al, 2020 ).…”
Section: Discussion Of Merged Resultsmentioning
confidence: 99%
“…Similar findings were reported in a study on a sample of Chinese respondents, who preferred to travel only a short distance to their destinations ( Zheng et al, 2021a ). Other pieces of research focusing on understanding tourists’ choices with regards to destinations found that tourists preferred to travel domestically, favouring proximity tourism to destinations less affected by COVID-19, and to places that were less crowded (Aiello, Bonanno, and Foglia, 2020 ), easily accessible (e.g., Lew et al, 2020 ), already known (Kock et al, 2020 ), and where well-established infrastructures and high-quality medical facilities were available (e.g., Wen et al, 2020 ). Furthermore, recent studies reported tourists choosing destinations allowing them to practice mountain tourism, second-home tourism, and outdoor tourism (Seraphin & Dosquet, 2020 ).…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Tesislerdeki insan yoğunluğuna göre kişisel tedbirlerini alacak olan tüketiciler maske, mesafe ve temizlik kuralları gereği kalabalıktan uzak durmaya, havuz yerine denizi tercih etmeye, sürekli tesis içinde kalmamaya çalışacaktır. Yapılan araştırmalarda tüketicilerin pandemi sürecinde deniz temelli tatil tercihlerinde sağlık ve güvenlik açısından havuz, sauna, hamam gibi yerleri pek kullanmadıkları (Bhakat, 2020;Budd & Ison, 2020) bunun yerine daha çok denizi tercih ettikleri ortaya çıkmış ve hatta her gün için oda temizliği istemedikleri (Awan, Shamim & Ahn, 2020;Bagnera, Stewart & Edition, 2020;Rosemberg, 2020), daha çok oda+kahvaltı tatil (Aiello, Bonanno & Foglia, 2020;Hofmeyr, 2020;Rosenthal vd., 2020) konseptini tercih ettikleri belirtilmiştir. Oluşan kaygı ve endişe nedeniyle diğer insanlardan mümkün olduğunca uzak durma eğiliminde olan tüketicilerin tatil zamanlarını daha çok tesis dışında geçirme düşüncesine sahip olduğu anlaşılmaktadır.…”
Section: Sonuç Ve Tartışmaunclassified